Decreased precipitation reduced the complexity and stability of bacterial co-occurrence patterns in a semiarid grassland - Wang, Jinlong; Wang, Chunjuan; Zhang, Jinwei; Wu, Xuefeng; Hou, Yu; Zhao, Guiyun; Sun, Haiming (Frontiers in Microbiology, 2022)
The grassland harbors complex bacterial communities, whose dynamic interactions are considered critical for organic matter and nutrient cycling, but little is known about how changed in precipitation impacts on bacterial interactions. We constructed co-occurrence networks for bacterial communities associated with the precipitation manipulation experiments in the Eastern Eurasian Steppe in China. The results showed that the network topological features of bacterial communities dramatic dissimilarity between increased precipitation, control and decreased precipitation. Bacterial co-occurrence pattern in increased precipitation was more complex and stable with great network size followed by control and decreased precipitation. Soil moisture was the major factor influencing the complexity, size, and stability of bacterial networks across different precipitation gradients, followed by total nitrogen (TN), belowground biomass, aboveground biomass and total carbon (TC). The networks with more keystone taxa were more complex and stable, and the number of key taxa has a similar trend to the complexity and stability of the network. Our results indicate that drought condition reduced the complexity and stability of bacterial community, that is, future changes in precipitation will greatly reshape the interactions of bacteria in semi-arid grasslands. Overall, these findings improve our understanding of how bacteria respond to changes in precipitation by regulating their interactions in semi-arid grassland ecosystems.